(untitled) (ItalianoLinguadue, 2021)
Nel breve saggio, al ricordo personale di importanti tappe della vita universitaria trascorse con Fabrizio, si accompagnano alcune considerazioni sull’arte della lettura di cui Fabrizio Frasnedi è stato un grande interprete e precursore, sia nella pratica didattica che performativa propria degli studi umanistici, sulla scia delle suggestioni di un Maestro come George Steiner. The talent of the reader In this short essay, personal recollections of important moments of university life spent with Fabrizio are accompanied by some considerations on the art of reading, which Fabrizio Frasnedi was a great interpreter and precursor of, both in his didactic and performative practice in humanistic studies in the wake of the suggestions of a Master like George Steiner.